ANALYSIS OF DEIXIS IN "DIE WITH A SMILE" BY BRUNO MARS AND LADY GAGA - Zahra Bil Nazzary; Pipit Rahayu; Eripuddin Eripuddin (JEE (Journal of English Education), 2025)
This thesis is entitled Ã¢â‚¬Å“Analysis of Deixis as Found in the Song Die With A Smile Bruno Mars Feat Lady GagaÃ¢â‚¬Â. In this research, the object used is the lyrics of Die With A Smile Bruno Mars Feat Lady Gaga. The purpose of this research is to find out the use of deixis found in the song Die With A Smile Bruno Mars feat Lady Gaga. This research is organized using a descriptive qualitative method. The result of this research can be concluded that, based on the data that has been presented, the use of deixis in the lyrics of Die With A Smile has successfully fulfilled its function and purpose as a whole. The researcher shows that the deixis not only strengthens cohesion and coherence in the text but also plays a vital role in conveying messages in a more precise and more structured way. With the right choice of words, the deixis in this song facilitates understanding for the listener or reader and enriches the meaning contained in the lyrics.